Peningkatan Pengetahuan Dan Mengasah Kemampuan Anggota Unit Kegiatan Mahasiswa Peradilan Semu - Patrick Corputty; Astuti Nur Fadillah (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Improving the knowledge and abilities of UKM members is not only obtained in the lecture hall, positive activities outside the classroom including discussions, seminars and other activities can be a reference to improve students' own abilities.Purposes of Devotion: This community service was intended to raise awareness that Maluku has five protected intangible cultural heritage, which were ratified by Presidential Regulation number 78/2007 concerning the Ratification of the Convention for the Safeguarding of Intangible Cultural Heritage, one of which is Traditional Liquor (SOPI), and it is hoped that the community will be able to well preserve this cultural heritage so that it can continue to exist in the community without causing any crime-related acts. Method of Devotion: Each presenter employed the lecture format. Lecturers were given time to present their subject, and then participants were given the opportunity to pose problems and ask questions, which were then answered in turn by the lecturers based on the content being questioned about.Results of the Devotion: This legal awareness counseling activity had a positive impact on the Bumey community, as evidenced by the active participation of participants through their questions and a greater understanding of legal awareness for partners, allowing the tridharma activities of lecturers to play a role in resolving problems encountered, one of which was how to preserve intangible culture by obeying the law so as to create a good legal culture that does not lead to crime as a result of excessive consumption of SOPI, which may hinder national development.